Carbonate Mineral Formation under the Influence of Limestone-Colonizing Actinobacteria: Morphology and Polymorphism - Cao, Chengliang; Jiang, Jihong; Sun, Henry; Huang, Ying; Tao, Faxiang; Lian, Bin (Frontiers in Microbiology, 2016)
Microorganisms and their biomineralisation processes are widespread in almost every environment on earth. In this work, Streptomyces luteogriseus DHS C014, a dominant lithophilous actinobacteria isolated from microbial mats on limestone rocks, was used to investigate its potential biomineralisation to allow a better understanding of bacterial contributions to carbonate mineralisation in nature. The ammonium carbonate free-drift method was used with mycelium pellets, culture supernatant, and spent culture of the strain. Mineralogical analyses showed that hexagonal prism calcite was only observed in the sub-surfaces of the mycelium pellets, which is a novel morphology mediated by microbes. Hemispheroidal vaterite appeared in the presence of spent culture, mainly because of the effects of soluble microbial products (SMP) during mineralisation. When using the liquid culture, doughnut-like vaterite was favoured by actinobacterial mycelia, which has not yet been captured in previous studies. Our analyses suggested that the effects of mycelium pellets as a molecular template almost gained an advantage over SMP both in crystal nucleation and growth, having nothing to do with biological activity. It is thereby convinced that lithophilous actinobacteria, S. luteogriseus DHS C014, owing to its advantageous genetic metabolism and filamentous structure, showed good biomineralisation abilities, maybe it would have geoactive potential for biogenic carbonate in local microenvironments.